Can relict-rich communities be of an anthropogenic origin? Palaeoecological insight into conservation strategy for endangered Carpathian travertine fens. (15th April 2020) - Hájková, Petra; Jamrichová, Eva; Šolcová, Anna; Frodlová, Jitka; Petr, Libor; Dítě, Daniel; Hájek, Michal; Horsák, Michal
Abstract: Western-Carpathian travertine fens developed on deep-circulation groundwater are highly localised and harbour unique communities that combine rare species of calcareous fens and salt marshes, with many species considered glacial or Early-Holocene relicts. Using a multi-proxy palaeoecological approach, we tested the assumption of naturalness and Holocene continuity of the current plant and mollusc communities occupying one of the best-preserved travertine fens in Europe. Our novel results, based on two complete cores throughout the fen deposits, document an anthropogenic origin of the current communities, despite their richness in rare and relict species. The habitat originated in the very beginning of the Holocene, later it was encroached by a semi-open woodland with spruce and alder and then by a dense reed bed that suppressed fen species even more than woodland encroachment. When compared with a fen site on shallow-circulation groundwater, the Holocene succession to woodlands has been blocked by travertine formation, allowing survival of light-demanding relicts in small patches. The current communities were established once the woody plants, and especially reed, were reduced by medieval land use. The community itself is therefore not relict, but it harbours probable descendants of relict populations that survived in neighbouring small refugia throughout the Holocene. Our results strongly support the need for active conservation actions as mowing and extensive grazing, mimicking the traditional type of land use, which has conditioned the recent travertine assemblages in the past. Highlights: Travertine fen communities are unique and rich in relict species. Palaeoecological approach may help to assess their naturalness and need of management. Late-glacial age with long wooded stage was revealed on a studied travertine site. Community itself is hence not relict, but it conserves a relict species pool. Anthropogenic origin of travertine communities calls for regular conservation action.